(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article mentions the role of grammar games that play a vital role in teaching foreign languages to students. Games help to improve grammar, vocabulary, listening, speaking, and even reading in an amusing way.